METAFORA DALAM LEMBAR OPINI, WUJUD KONGKRET GAMBARAN PERUBAHAN BAHASA - Diana Tustiantina (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
Language change is reasonable due to the inability of speakers to remember how they spoke ten or twenty years ago. In addition, the speakers tend to set aside our differences do not impede meaning in communication. Language Change is not visible, but we can find evidence to show that a language has changed. Changes can be seen from the source language written and oral. From these two sources, the primary source of evidence of language change is a written record. This study tried to describe the data is a metaphorical expression of discourse opinion pieces using metaphor theory proposed by Lakoff and Mark (2003: 3). This research data is part of the discourse in the form of opinion pieces in the weekly news magazine “Tempo” edition of 13 to 19 April 2009, which has a metaphorical expression. Discussion of the results showed that the change in language can be shown through the use of metaphor in written evidence.